Management of Secondary and Micro-Nutrients for Enhancing Crop Production in Odisha - Singh, M. V.; Behera, S. K.; Jena, D. (Indian Farming, 2015)
Odisha is an important state in eastern India having vast potentials for increasing crop pproductivity. Acid soils of Odisha can be managed by addition of 1/10 of the lime requirements. Defiency of zinc, boron, molybdenum and sulphur are more conspicuous. Crops need to be fertilized with boron, sulphur, zinc to soil and molybdenum seed treatment in different cropping system. Vegetables and coconut grown in red and laterite soils need more boron compared to black soils. Application of 40-45 kg S/ha through phosphogypsum is found beneficial to major cereal , oilseeds, pulses and vegetable crops and found more beneficial.